3D printed-poly(lactic acid) scaffolds with improved bioactivity for bone tissue engineering - Teixeira, Bruna Nunes (2017)
PLA scaffolds produced by 3D printing are a promising alternative to bone tissue engineering. A simple mussel inspired method, polydopamine (PDA) surface functionalization, has being proposed as an efficient way to enhance the bioactivity of biomaterials, such as PLA, and to promote covalent immobilization of a variety of proteins such as collagen (COL) type I. This study aimed to characterize PLA scaffolds produced by FDM with different pore size, concomitantly to the influence of PDA coating as platform to enhance the bioactivity and the immobilization of COL I onto printed PLA. Scaffolds geometry influenced directly in the porosity and compressive strength of printed parts. The PDA layer improved the COL immobilization onto the surface of PLA scaffolds in 92% and enhanced the adhesion of porcine Bone Marrow Stem Cells (MSCs). The combination of PDA and COL layers provided the best conditions for early stage cell adhesion and proliferation. Cells cultured onto PDA/COL scaffolds produced substantially higher amounts of Alkaline Phosphatase (ALP), a marker of osteogenesis, by 21 days in culture. Scaffolds with projected pores of 700 µm in size (strut spacing = 1 mm) and coated with PDA plus COL I provides appropriate porosity, mechanical properties and biological conditions to allow bone tissue regeneration.